Alteration in antioxidant status and lipid peroxidation of sheep previously treated with vitamin A and ?-carotene during breeding and periparturient period - Kamiloglu, Nadide Nabil; Beytut, Ebru; Aksakal, Mesut (Natl Veterinary Research Inst, 2006)
The aim of this study was to determine changes in the erythrocyte antioxidant defence system and in lipid peroxidation as thiobarbituric acid reacting substance (TBARS) in sheep treated with vitamin A and P-carotene. Thirty-two healthy female and 4 healthy male Tuj sheep, aged 4-5 years, weighing approximately 57 kg each were used in the study. The females were divided into four equal groups. The oestrous cycles of the ewes were synchronized by the application of sponges containing medroxyprogesterone acetate and by the intramuscular administration of 500 IU of PMSG. Twenty-four hours after the injection of PMSG, a ram was added to each group and allowed to mate with the sheep. The first group was used as the control and given Freund's adjuvant incomplete as a placebo. Eight miligrams/kg of beta-carotene (group II), 200 000 IU of vitamin A (group III) and a combination of 100 000 IU of vitamin A and 4 mg/kg of beta-carotene (group IV) were administered intramuscularly 15 d before parturition. Blood samples were obtained from the jugular vein at 2 d intervals for 35 d, in order to measure the levels of vitamin E and lipid peroxidation in plasma and the activity of glutathione peroxidase (GSHP(X)) and levels of glutathione (GSH) in erythrocytes. The plasma TBARS level began to increase on day 3 of breeding, reaching its highest value on day 7 after parturition. However, this increase was lower in the experimental groups than in the controls. Erythrocyte GSHPx activity increased in groups II and IV compared with the control group on day 3 of breeding (P < 0.001). This increase was higher in group II than in the other groups. Although GSH-P-X activity increased ill the vitamin A group after parturition, vitamin A injection did not affect the activity before parturition and during breeding. Erythrocyte GSH levels started to increase oil days 4, 6, and 9 after injection in groups II, IV, and III, respectively. The GSH levels in the experimental groups showed a significant increase on day 3 of breeding as compared with the control group (P < 0.01). There was a slight decrease ill the GSH levels in all groups after parturition. However, this decrease was lower in the experimental groups than in the controls. A statistically significant difference ill the levels of vitamin E in groups II and IV in comparison with the control group was observed on days 3 and 5 of breeding (P < 0.05, P < 0.01). It was also observed that vitamin E levels changed in the treated groups in relation to the examined periods. We found also that the levels of vitamin E were little affected by injections of vitamin A. Our findings indicate that increased free radical scavenging activities obtained after vitamin A and P-carotene injections may have supported the antioxidant defence system during and after parturition of the sheep.
Keywords: sheep; antioxidants; lipid peroxidation; vitamin A; beta-carotene; breeding